An assessment of rural health care delivery system in some areas of West Bengal-An overview - Sandip Kumar Ray; Subhra S Basu; Amal Kumar Basu (Wolters Kluwer Medknow Publications, 2011)
A cross sectional observational study was carried out in three districts of West Bengal by following observational, quantitative and qualitative methods during July to December 2006 to find out the extent of utilization, strengths, weaknesses and gap as well as suggest recommendations in connection with health care delivery system for the state of West Bengal, India. A total of 672 episodes of illnesses were reported (2 weeks recall) by the study population of the three selected districts in three geographically separated divisions of West Bengal. None did seek care from any health facilities for treatment in case of 221 (32.89%) episodes; especially from tribal areas where in case of 76.19% none sought any health care from any facilities depended on their home remedies. In rest of episodes the (451), majority preferred government health facilities (38.58%), followed by Unqualified quacks (29.27%) due to low cost as well as living in close proximity, 27.27% preferred qualified Private practitioners and only 4.88% preferred AYUSH, as a first choice. Referral was mostly by self or by close relatives/families (61%) and not by a doctor. Awareness is required to avoid unnecessary referral. Cleanliness of the premises, face-lift, and clean toilet with privacy and availability of safe drinking water facilities could have an improved client satisfaction in rural health care delivery systems. This could be achieved through community participation with the involvement of PRI. However, as observed in the study RCH services including Family Planning as well as immunization services (preventive services) were utilized much better while there was a strong need of improvement of Post Natal Care, otherwise, Neonatal and Maternal mortality and morbidity will continue to be high.